Value Creation Through Business Model Innovation : A Case Study of Connect Broadband - Bashir, Makhmoor; Verma, Rajesh (Prabandhan: Indian Journal of Management, 2017)
This paper attempted to clarify how business model innovation can be a great source of value creation in businesses using a case study on â€œConnect Broadband,â€ a data service provider headquartered in Mohali, Punjab, India. Connect Broadband in 2014 became the first company in the history of broadband industry to innovate their existing business model by combining antivirus solutions with data services and as a result, their penetration rate increased by more than 50% and the revenues also saw a huge surge. The company also added 40,000 - 45,000 customers in no time. This business model innovation took the company to the second position in the market with reference to the customer base or market share in Punjab, coming behind Bharat Sanchar Nigam Limited (BSNL), a government owned subsidiary.